KEMAMPUAN DECISION MAKING SISWA SMA DALAM PEMBELAJARAN FISIKA BERBASIS INKUIRI TERBIMBING - Alivea Pisca Dianty; Supeno Supeno; Sri Astutik (Universitas Jember, 2020)
Students must be able to make decisions effectively in urgent conditions and be able to formulate strategies to take action in an effort to make the situation under control. During learning at school, there are still many students who tend to be more receptive to information than to provide solutions that can solve the problems. The ability to make decisions can be trained using the guided inquiry learning model, because the essence of the guided inquiry strategy is relate to the decision making skills. The use of guided inquiry models in learning can increase student to think critically, be more productive, be more skilled in obtaining information and making decisions. The research aims is to know the ability to take the decision making of students high school in learning physics based on guided inquiry. This type of research was descriptive research. This research is used to describe the participation of high school students in making decision on guided inquiry on physics learning. The results obtained by the study of guided inquiry learning models can increase student participation in making decisions.